Prevalence and factors associated with bacterial vaginosis in women in Brazil: a systematic review - Cristina de Camargo, Kélvia; Ribeiro Figueiredo Alves, Rosane; Aparecida Saddi, Vera (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: Bacterial vaginosis is characterized by the imbalance of the vaginal flora, with decrease in Lactobacillus and increase in other bacteria. Objective: To investigate the prevalence and factors associated with bacterial vaginosis. Methods: Systematic review based on the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, filed in the International Prospective Register of Systematic Reviews. The research was conducted in the PubMed and Scopus databases in September 2021. After reading the titles and abstracts of 84 articles and the full text of 20 articles, 10 of them were included in the review. The articles were considered eligible if they investigated the prevalence of bacterial vaginosis and used Amsel's diagnostic criteria or Gram-stained bacterioscopy in women of reproductive age without comorbidities. The studies were evaluated by two investigators to establish reliability. The risk of bias and the quality of the selected studies were evaluated using the Joanna Briggs Institute tool. Results: The mean prevalence of bacterial vaginosis in the included studies was 25.4% (95%CI 24.0–26.8). In three population-based studies, the mean prevalence was 18.1% (95%CI 16.0–20.5); and in seven clinic-based studies, it was 27.2% (95%CI 24.6–29.9). The factors associated with bacterial vaginosis were the use of sex accessories (OR 2.4; 95%CI 1.1–4.9), marital status “single” (OR 1.4; 95%CI 1.1–1.8), partner infidelity (OR 1.5; 95%CI 1.2–1.9), abnormal vaginal secretion (OR 1.5; 95%CI 1.2–2.0), and the presence of trichomoniasis (OR 4.1; 95%CI 1.5–11.5). Conclusion: The prevalence of bacterial vaginosis was high, and the associated factors are linked to sexual behavior.